Effects of Microplastics on Germination and Seedlings Growth of Wheat (Triticum aestivum L.) (Journal of Bio-Science, 2026)
Microplastics pose a serious threat to both ecosystems and human health. It is increasingly detected in agricultural soil but how these microplastics affects on plant growth system that has remained poorly understood. The present investigation was assessed the effect microplastics in wheat (Triticum aestivum L.) seedlings growth. Different microplastics in aqueous solution showed varied response on wheat seedlings growth.   It was noted that after 10 days of  seedlings growth in petri dishes, the WMRI-I wheat showed maximum efficiency of germination percentage (87.5%), shoot elongation (6.68 cm), root elongation (6.62 cm) and lateral root formation (4.38 roots/seedling) than WMRI-II and WMRI-III. At all the cases, the minimum growth response was noticed in WMRI-III wheat. The F-value reveals that shoot and root length were significantly different towards microplastic treatments. The present findings also indicate that PPLCW (microplastic plus polythene) treatment had more negative impact on wheat seedlings growth.J. Bio-Sci. 33(2): 51-56, 2025